Problematika Pendidik Dalam Mengimplementasikan Kurikulum Merdeka - Sunardi; Erfan Yudianto; Nurcholif Diah Sri Lestari; Andini Luluk Nofitarini; Rima Dwi Oktaviani; nabilatul hafidhoh (Jurnal Intelek Dan Cendikiawan Nusantara, 2024)
Most classes in Indonesia are heterogeneous classes, which must be a challenge for educators in implementing this independent curriculum. Therefore, this study aims to describe the probematics of educators in implementing the independent curriculum. This type of research is descriptive qualitative with the subject of 16 educators at the secondary school level in Jember Regency. The instrument used is a questionnaire collected using the questionnaire method with google form media which contains 17 questions. Based on the results of the analysis, it was found that there were problems in implementing the independent curriculum, namely 1) Lack of training on the independent curriculum. 2) Difficulty formulating the flow of learning objectives. 3) Knowing the needs of individual students. 4) Carrying out assessments.